THE EFFECT OF CURRENT RATIO AND DEBT TO ASSET RATIO ON RETURN ON ASSET AT PT SEPATU BATA TBK 2014–2023 - Rina, Nova; Daud Ibrahim, Marwah; Widya Dini, Winda (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This study aims to determine the effect of the Current Ratio (CR) and Debt to Asset Ratio (DAR) on Return on Assets (ROA) at PT Sepatu Bata Tbk for the period 2014–2023. This study uses a quantitative approach with an associative type. The data used are secondary data in the form of the company's annual financial reports, which were analyzed using multiple linear regression with the help of SPSS version 27. The t-test results indicate that the Current Ratio has a positive and significant effect on Return on Assets, while the Debt to Asset Ratio has a significant negative effect. However, the F-test indicates that the Current Ratio and Debt to Asset Ratio simultaneously have a significant effect on Return on Assets. The coefficient of determination (R²) value of 0.613 indicates that 61.3% of the variation in ROA can be explained by the two independent variables. Based on these findings, it is recommended that management pay more attention to liquidity management and the company's funding structure. This study also contributes to academics and practitioners in understanding the relationship between financial ratios and profitability